CT-Based assessment of sarcopenia and its association with biologic treatment outcomes in Chinese Children with Crohn's disease - Guo, Cheng; Kong, Yan; Wang, Guoli; Du, Junye; Yu, Chang; Wu, Jie (Frontiers in Nutrition, 2025)
BackgroundSarcopenia affects treatment outcomes in patients with Crohn's disease (CD), yet research focusing on pediatric populations is limited. This study aimed to determine the prevalence of sarcopenia among Chinese children with CD and to evaluate its impact on biologic therapy by analyzing body composition parameters based-on computed tomography enterography (CTE).MethodsPediatric CD patients who underwent CTE and received infliximab (IFX) treatment between 2022 and 2025 were enrolled. Clinical, laboratory, and radiological data were collected. CTE was utilized to assess body composition. The control group consisted of children without inflammatory bowel disease (non-IBD) who underwent abdominal CT scans.ResultsA total of 68 children with CD (mean age 11.89 years) were included. The prevalence of sarcopenia was significantly higher in the CD group compared to the 136 controls (33.8% vs. 10.2%, P = 0.001). Body mass index (BMI) was identified as the only protective factor against sarcopenia (OR 0.734, 95% CI 0.578–0.932, P = 0.005). Among CD patients, those with loss of response (LOR) to IFX had a significantly higher incidence of sarcopenia than those in remission (50% vs. 23.8%, P = 0.027). After treatment with infliximab combined with total exclusive enteral nutrition (EEN) or partial enteral nutrition (PEN) in 44 children, follow-up CTE showed a significant reduction in sarcopenia prevalence (47.7% vs. 25%, P = 0.027).ConclusionSarcopenia is common in Chinese children with CD and adversely affects the efficacy of biological therapy. CTE is a valuable tool for assessing sarcopenia in this population. Early detection and intervention may improve clinical outcomes for children with CD.